PENGARUH KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ 45 - Istanti, Sri Layla Wahyu (potensio, 2013)
This study examines the effect of dividend policy on stock prices on companies LQ 45 in 2004-2008. Selection of LQ 45 firms as stocks of companies included LQ 45 is a liquid stock and include top ranking of a number of outstanding shares in the Indonesian Stock Exchange. This study uses a simple regression analysis techniques. The results showed that the positive effect of dividend policy on stock prices, but the effect is very small. The conclusion of this study is the dividend policy is not the only factor affecting stock prices, but there are other factors that influence, namely macro and micro economic factors.Â Keywords: dividend policy, stock price